PENANGANAN PASCA PANEN BUAH-BUAHAN DAN SAYURAN - Siswadi - (Innofarm:Jurnal Inovasi Pertanian, 2007)
ABSTRACT Horticulture is the designation of category plant fruits, vegetables and ornamental plants. As  Characteristics  of  horticultural  products  the  plant  fruits   and  vegetables  are   perishable products that need a proper post-harvest handling. Post harvest handling is needed to maintain the quality of the results so that when consumed gisinya value does not go down, but  farmers in Indonesia have not been able to do post-harvest handling of fruits and vegetables correctly, due to the limitations  they. Variety of ways post-harvest handling of fruits and vegetables is a beginning of cooling (recooling), sorting, washing, fumigation, packaging and storage. Key word :  post harverst fruits and vegetables